Wave-transparent composites based on phthalonitrile resins with commendable thermal properties and dielectric performance. (3rd June 2020) - Zu, Yuan; Zhang, Fengfeng; Chen, Dandan; Zong, Lishuai; Wang, Jinyan; Jian, Xigao
Abstract: Wave-transparent composites with resin matrix are urgently required for the aerospace industry because of lightweight and facile formation. Many thermosetting resins could serve as the matrix of wave-transparent composites, however, some of them are suffering from harsh synthetic conditions, low service temperature (lower than 400 °C), and unstable dielectric properties at high temperature. Herein, branched phthalonitrile resins matrix based on 1, 3, 5‐tris(4‐fluorobenzoyl)benzene with excellent solubility was prepared by a facile polycondensation procedure. The 5% weight loss temperature of the cured network was as high as 553 °C. Besides, the quartz fiber reinforced composite simultaneously exhibited superior service temperature (over 500 °C) and stable dielectric properties over a broad temperature range from 25 °C to 500 °C. These results would strongly suggest such phthalonitrile resins as excellent wave-transparent composite matrix in those high-tech applications such as aerospace electronics and devices. Graphical abstract: Image 1 Highlights: New branched Phthalonitriles were prepared based on a trifunctional monomer. Oligomers exhibited good processability for prepreg and hot-press manufacture. Cured thermosets possessed superior thermal stability ( T g  > 500 °C, T d5% >550 °C). Branched PN/QF composites had the stable dielectric properties at 500 °C.